Analysis Of Juvenile Delinquency Based On Travis Hirschi's Social Control Theory In Batam City - Mely Sisca; Abdurrakhman Alhakim (LEGAL BRIEF, 2022)
Juvenile delinquency is a collection of various juvenile behavior that is unacceptable in society which is usually a criminal act. There are 2 forms of juvenile delinquency, namely delinquency committed at school and outside school, juvenile delinquency in school in the form of skipping school, crossing walls, brawls, etc., while juvenile delinquency outside school is usually in the form of smoking, free sex, illegal racing, drunkenness, taking drugs, stealing, killing, and other harmful behavior. To find out how to analyze juvenile delinquency in terms of Travis Hirschi's social control theory and what are the criminal sanctions against juvenile delinquency in Batam City. The method used in the following article is a juridical-empirical approach which uses data collection techniques with google form which has a total of 180 respondents from Batam City. The results of this study prove that the role of affection from parents is very important.